ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA DITINJAU DARI GAYA BELAJAR VAK PADA MATERI PENCEMARAN LINGKUNGAN - Fatima, Siti; Tamam, Badrud; Hadi, Wiwin Puspita; Ahied, Mochammad; Rosidi, Irsad (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
The purpose of this study was to determine the creative thinking ability of students at SMP Negeri 1 Sepulu, Sepulu district, Bangkalan regency in terms of the VAK learning style on environmental pollution material. The research used a type of qualitative dscriptive research carried out at SMP Negeri 1 Sepulu with a population of all classes VII for the 2021-2022 school year. The sampling technique uses purposive sampling. The research sample taken was 29 students. Data were collected using creative thinking skills tests, learning style questionnaires and interviews. Based on the results of the study it can be concluded that: At SMP Negeri 1 Sepulu there are 14 students with a visual learning style, 5 students with an auditorial learning style and 10 students with a kinesthetic learning style. The ability to think creatively based on visual learning styles has an average score of 65 with good criteria, an auditorial learning style averages a score of 74 with good criteria and a kinesthetic learning style with an average score of 71 good criteria.